The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.5937/zasmat2001060r
|View full text |Cite
|
Sign up to set email alerts
|

Ecological alternatives to conventional dyeing of cotton with reactive dyes

Abstract: Cotton dyeing is usually performed by reactive dyes by exhaustion method. Great quantities of salts and alkalis used in the formulation of dyeing bath eventually get into the watercourses and negatively affect the environment. In this work, studied are the possibilities of reducing salt and alkali concentrations in the dyeing bath in order to reduce water pollution after the dyeing process and soap washing. The obtained results show that the alternative procedures are environmentally more favorable, which is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…The next step is to optimize the surface functionalization techniques to incorporate the desired type and amount of the reactive functional group [19,[21][22][23]. Considering the importance of polyester as a synthetic polymer in this research, before treatment with chitosan, polyester materials can be modified by UV irradiation [23], plasma pretreatment [24,25], enzymatic treatments [26], or alkaline hydrolysis prior to treatment with chitosan to activate the surface and increase the hydrophilicity of the polymer structure [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The next step is to optimize the surface functionalization techniques to incorporate the desired type and amount of the reactive functional group [19,[21][22][23]. Considering the importance of polyester as a synthetic polymer in this research, before treatment with chitosan, polyester materials can be modified by UV irradiation [23], plasma pretreatment [24,25], enzymatic treatments [26], or alkaline hydrolysis prior to treatment with chitosan to activate the surface and increase the hydrophilicity of the polymer structure [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Alkaline hydrolysis of polyester fibers in the alkali is a traditional high-efficiency pretreatment process that takes place on the surface [10,[26][27][28]. Some studies have shown that alkaline hydrolysis can improve the coating of functional polymers to form fine roughness of polyester [12,30].…”
Section: Introductionmentioning
confidence: 99%
“…The reactive dyes have the ability to form covalent bonds with the material fibers through a nucleophilic mechanism [2]. Most dyes are ecologically hazardous [3] and toxic to human health [4]. The human body comes in daily contact under any circumstance with these reactive dyes through clothing, underwear made of cotton.…”
Section: Introductionmentioning
confidence: 99%